2018
DOI: 10.1002/brb3.1091
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler to detect right‐to‐left shunt in cryptogenic acute ischemic stroke

Abstract: ObjectivesWe aimed to confirm the sensitivity and specificity of contrast transcranial Doppler (cTCD) in the detection of right‐to‐left shunt (RLS) compared to the current reference standard (i.e., transesophageal echocardiography—TEE) in patients aged <55 years with a cryptogenic acute ischemic stroke (AIS) or high‐risk (ABCD 2 score ≥4) transient ischemic attack (TIA), and to calculate the real life delay in detecting RLS by cTCD versus TEE in a tertiary care academic stroke center.MethodsConsecutive 16‐ to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Cumulatively, PFO was documented in 186 of 1,267 (14.7, 95% CI = 12.8-16.7) healthy subjects/controls, in 66 of 131 (50.4, 95% CI = 41.9-58.8) patients with CE, and in 11 of 125 (8.8, 95% CI = 4.8-15.2) patients with non-CE. In our review, we included 12 TCD studies (58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69). Three studies were conducted in migraineurs compared to a healthy population (59)(60)(61), and nine studies reported data from patients with cerebrovascular events, of which five studies (63-67) also included TIAs (20-75% of the total events).…”
Section: Resultsmentioning
confidence: 99%
“…Cumulatively, PFO was documented in 186 of 1,267 (14.7, 95% CI = 12.8-16.7) healthy subjects/controls, in 66 of 131 (50.4, 95% CI = 41.9-58.8) patients with CE, and in 11 of 125 (8.8, 95% CI = 4.8-15.2) patients with non-CE. In our review, we included 12 TCD studies (58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69). Three studies were conducted in migraineurs compared to a healthy population (59)(60)(61), and nine studies reported data from patients with cerebrovascular events, of which five studies (63-67) also included TIAs (20-75% of the total events).…”
Section: Resultsmentioning
confidence: 99%
“…However, transesophageal examination is very often a great discomfort for the patient. It is also emphasized that some venous-arterial shunts (RLS -right -left shunts) may be overlooked in TEE due to the difficulties in performing the Valsalva maneuvre by patients [11,14]. Transesophageal echocardiography is an invasive examination, carrying a risk of potentially dangerous complications.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative to transesophageal echocardiography for detecting a venous-arterial shunt, is contrast enhanced ultrasound Doppler examination of intracranial arteries and arteries supplying the head ('blind doppler', Transcranial Doppler -TCD), which as a cheap, noninvasive and safe method characterized by very high sensitivity and specificity (97% -100% and 93-98% respectively) [11,14,16], and which may significantly improve the detection of cases of PFO with venous-arterial shunt and enable screening of divers and candidates for divers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations